Solid state chemistry for developing better metal-ion batteries - Artem M. Abakumov (Nature Portfolio, 2020)
The development of high performing metal-ion batteries require guidelines to build improved electrodes and electrolytes. Here, the authors review the current state-of-the-art in the rational design of battery materials by exploiting the interplay between composition, crystal structure and electrochemical properties.